Uji Pertumbuhan dan Produksi Beberapa Genotipe Tanaman Tomat (Lycopersicum esculentum Mill.) di Dataran Rendah - Silvia, Rini; Zuhry, Elza; ', Adiwirman (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
cultivated tomato varieties those well adapted to the growing environment. Varieties have different levels of sensitivity to environmental conditions. The result will be reach the maximum level when cultured in a suitable environment. The objective of this research was to find the genotypes of tomato that has good growth and yield in the low land. This research use Completely Block Randomized Design (CBRD) that consists of 6 treatments and 3 replications. These treatments consist of 6 genotypes, those IPB T34-7-7, IPB T3-8-10, IPB 2201-5-8b, IPB T64-2-2(1), Karina and Ratna. The result of this experiments suggest those the genotype significantly affect (days to flowering, harvesting time, plant height, stem diameter, weight per fruit, fruit length, fruit diameter, fruit flesh thickness, number of fruit cavities, and total weight per plant), affect number of fruit cavities however genotype did not significantly. The experimental result showed those genotypes IPB T3-8-10 has the highest total fruit weight (701.1 g) compared to Ratna and Karina. Genotypes IPB 2201-5-8b has the lowest total fruit weight (174.0 g). Key words : Growth, Lycopersicum esculentum, genotypes, low level land